A CASE OF DUODENAL BULB ULCER FORMATION IN A JUDO SPORTSMAN - Avramenko, A. A.; Magdenko, A. K. (Rehabilitation and Recreation, 2025)
The research aims to study and give a pathophysiological explanation for the case of duodenal ulcer formation in an athlete involved in judo. Research methods: clinical and anamnestic, instrumental, histological, and bacteriological. The results. During the anamnesis collection, it was found that the patient had been periodically experiencing heartburn after eating spicy food since the age of 13. The clinical manifestation (dull pain in the epigastrium), with which he consulted a gastroenterologist, arose after the patient, during an active workout that took place 3 days before consulting a doctor, sharply and rhythmically tensed all muscles, including the abdominal muscles, for 30 seconds while escaping from an opponent's hold. When analyzing the acidity level data, it was found that the patient's acidity corresponded to subtotal normacidity. After endoscopy, a typical ulcerative defect was detected in the duodenal bulb. Histology data confirmed the presence of chronic gastritis in the active form (+++). Testing for HP infection revealed the presence of bacteria in an active form at a high concentration (+++) on the mucosa in all 4 topographic zones of the stomach, which confirms the presence of chronic non-atrophic gastritis in the patient in an active form at the time of the formation of the ulcer defect. Conclusions. The obtained data fully fit into the understanding of the mechanism of ulcer defect formation in the duodenal bulb according to the theory of «caustic alkaline spit». Timely detection and treatment of chronic non-atrophic gastritis in athletes experiencing heavy physical exertion prevents the formation of ulcers of the duodenal bulb and their complications.